Neighborhood racial and ethnic change in the United States from 1970 to 2010: an application of the Modified Lilien Index. Issue 3 (3rd July 2022) - Jaramillo, Atticus; Lester, T. William
ABSTRACT: This paper describes how the Modified Lilien Index (MLI) can be used to measure the rate of neighborhood racial and ethnic change. The MLI is useful because it measures the rate of change across multiple racial and ethnic groups. It also weights the rate of change for each neighborhood based on changes in the racial and ethnic composition of the entire population, which helps contrast neighborhoods undergoing high and low rates of change compared to the nation as a whole. Using harmonized census data, we demonstrate the utility of the MLI by analyzing neighborhood change across four groups—White, Black, Latino, and Asian—from 1970 to 2010. We find that the rate of racial and ethnic change decreased substantially during this time period, but also that there is significant variation in this trend at the regional and metropolitan level. Based on these results, we suggest that the MLI can be used to identify emergent geographies of neighborhood racial and ethnic change within a broader territory and to quantify how change impacts community structure and the outcomes of individuals.